Oxybelis wilsoni, a new species of vine snake from Isla de Roatán, Honduras (Serpentes: Colubridae) - Villa, Jaime D (1995)
A new species of Oxybelis is described from Isla de Roatán, Honduras. It differs from all species of Oxybelis in its tan to golden yellow coloration, in having a higher number of subcaudals as well as in other details of color and scutellation. The new species is closely related to O. fulgidus and is thought to be derived from afulgiduslike ancestor (i.e., is the sister species to fulgidus) that has been isolated in the area of its present range probably since the very late Pliocene. The presence of a yellow population of Oxybelis on Isla de Roatán, Honduras, has long been known (Keiser 1969). The status of this insular population has remained uncertain pending the acquisition of additional material (Keiser 1969, Wilson and Meyer 1985). We recently visited Isla de Roatán a number of times and obtained a large series of additional specimens. After examining this new material, and the previously known specimens from this island, we believe that this population represents an undescribed taxon, which should be known as